Mekanisme Survival Strategi: Antara Tekanan dan Fleksibilitas, Studi tentang Respon Petani Tembakau Terhadap Birokratisasi Perkebunan di Kali Tengah - Subando Agus Margono (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1998)
The State-owned Plantation Company 10 (PTPN X) constitutes an example of modem (rational) way in managing Vorstenkmds tobacco production in Indonesia. This case shows that as public bureaucracy becomes a part of international market, there is change of decision making locus in the society, from family institutions to the bureaucracy. Consequently, bureaucracy intervenes much of family institutions. There are two types of bureucratic intervention: economic and technical. Economic intervention is concerned with marginalization of income while technical intervention is concerned with marginalization in setting up the standard of quality for tobacco. The negative repercussion of these interventions has been a deteriorating spirit in planting tobacco among the farmers. Farmers become the outsiders in their own land. Then, because of pressure and insecurity, farmers try to respond by using social security mechanism through family institutions, both temporary and continually. Such developed social mechanism has been performing very well in connecting farmers with the market. Finding in Kali Tengah shows that traditional social security would necessarily be a continual dichotomy with modem social security.